Efficacy of a Novel Rotary System in Reduction of Intracanal Bacteria: An in Vitro Study - Vossoghi, Maryam; Vossoghi, Mitra; Shahriari, Shahriar; Faramarzi, Farhad; Yousefi Mashouf, Rasoul; Farhadian, Maryam (Iranian Endodontic Journal, 2016)
Introduction: This in vitro study aimed to assess the effectiveness of a single-file rotary system (OneShape) in reduction of intracanal bacteria. Methods and Materials: Eighty one single-rooted mandibular first premolars with single canals were used. Six samples were selected as aseptic control group. Seventy five remaining specimens were infected by Enterococcus faecalis and incubated for 72 h at 37°C. Then they were randomly divided into three groups (n=25). In each group, cleaning and shaping procedures were done using either two conventional rotary systems (ProTaper and iRace), or the single-file system (OneShape). Microbial samples from the intracanal environment were taken by paper points in two steps, before and after instrumentation. Then, they were diluted and plated in blood agar. In order to compare bacterial reduction and turbidity, the Kruskal-Wallis test was used followed by the Chi-Square and Mann-Whitney tests for pairwise comparison. The level of significance was set at 0.05. Results: The control group didn’t show any bacterial growth. The pre- and post-instrumentation samples were significantly different between three groups (P=0.02). Hence, there was no significant differences between turbidity of samples (P>0.05). Conclusion: OneShape system is efficient in bacterial reduction. In this regard ProTaper is the most effective system in intracanal bacterial reduction followed by iRaCe and OneShape, respectively. Keywords: Enterococcus faecalis; iRace; OneShape; ProTaper